The Effects of Supervision, Professional Attitude, and Digital Literacy on Counselor Performance - Hadi, Muhtar; Sugiyo, Sugiyo; Japar, Muhammad (Jurnal Bimbingan Konseling, 2023)
Counselor performance greatly determines the quality of education. Some aspects to consider in assessing this performance are the results of supervision by the school principal, a professional attitude and good digital literacy in the counselor. Regarding this matter, the current study aimed to analyze the influence of supervision, professional attitude and digital literacy on the performance of Vocational High School or SMK counselors using regression analysis. It involved 140 counselors at SMK as the subject selected using a proportional random sampling tehcnique. Their responses were recorded using questionnaires to be the quantitative data. In addition, the questionnaires were in form of the scales of supervision, professional attitudes, digital literacy, and performance. Since the data were quantitative, the design of this study was ex post facto. After being analyzed, the findings revealed supervision, professional attitudes, and digital literacy significantly affected the performance of vocational guidance and counseling teachers. Hence, it is expected that school principals will continue to improve academic supervision, while counselors are suggested to improve professional attitudes and digital literacy.